Solid‐State Lighting: Photoluminescent Materials for Solid‐State Lighting: State of the Art and Future Challenges (Advanced Optical Materials 4/2015). Issue 4 (April 2015) - Meyer, Jörg; Tappe, Frank
<x xml:space="preserve">Abstract</x> On page 424, J. Meyer and F. Tappe discuss the generation of white light from blue LEDs and luminescent materials with respect to currently available phosphors. Here, a rendered volume of a state‐of‐the‐art LED is obtained by X‐ray computed tomography (CT), to plan the preparation of microsections for more in‐depth analysis. Inset, left to right: brightfield contrast in LM, overlay of luminescence contrast, and backscattered electron energy dispersive X‐ray fluorescence mapping. Support by Prof. C. Thomas and T. Ogbazghi for microscopy and CT image acquisition is gratefully acknowledged. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>